(3EJMGa GdNjQI GdegQI HRhGFO GdeSGfjO GdYTQIs - (3CMeO Hf CHi HcQ Hf YHO GdQMef Hf ESeGYjd Hf Sdje GdcfGfi GdHhUjQi, TgGH GdOjf CHh GdYHGS,J (B840 (3g` s
(3ChdgG (B:s
(3JHJOF HcJGH GdJQgjH ef GdHNd hGdTM s
(3BNQgG (B:s
(3JfJgi HHGH GdCfHjGA CMjGA ai bHhQge , hgh BNQ GdcJGH s
(3GdeLdOI GdCNjQIs
(3hgPg GdfSNI dgG fSNI ecQQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B175s
Keywords: (3GdMOjK h GdeUWdMs